CHB multilevel inverter with sliding mode controller for DSTATCOM applications - Chenchireddy, Kalagotla; Jegathesan, Varghese (Institute of Advanced Engineering and Science, 2023)
In this article, the robust nonlinear controller for cascaded H-bridge-based distributed static compensator (DSTATCOM) with input-output linearization and sliding mode control scheme using an improved voltage balancing scheme is presented. The feedback linearization method and sliding mode control scheme are used to cancel nonlinearities and deal with invariant stability due to mathematical modeling uncertainties due to DSTATCOM parameter and external load disturbance. The improved voltage balancing is used to balance the voltages of the DC side capacitor of DSTATCOM. The complete simulation studies are out to validate the control scheme based on the improved voltage balance integrated with sliding mode control under disturbances caused by the load changes and DSTATCOM parametric changes. The performance characteristics of the DSTATCOM with sliding mode controller are tested using the MATLAB/Simulink platform.